Anorexia nervosa e bulimia nervosa: a abordagem cognitivo-construtivista de psicoterapia - Cristiano Nabuco de Abreu; Raphael Cangelli Filho (Psicologia, 2005)
Of the Eating Disorders, Anorexia Nervosa and Bulimia Nervosa are the ones that most frequently have made teenage, usually female patients seek for help. This help is provided through treatment by a multidisciplinary team, which consists of psychologists, psychiatrists, and nutritionists. Psychotherapy has shown to be one of the most effective components for improvement of patients suffering from bulimia nervosa and for anorexia nervosa cases, although further studies are needed. Thus, the goal in this text is to discuss (a) the premises involving the theoretical-practical bases of the cognitive-constructivist approaches; (b) the most commonly seen psychological characteristics of these patients; (c) psychological service (protocols) programs developed by the author; and finally, (d) the general conclusions drawn through the clinical practice involving results and other considerations.